Identification of an African swine fever virus gene with similarity to a myeloid differentiation primary response gene and a neurovirulence-associated gene of herpes simplex virus. - Sussman, M D (1992)
Here we describe an open reading frame (LMW23-NL) in the African swine fever virus genome that possesses striking similarity to a murine myeloid differentiation primary response gene (MyD116) and the neurovirulence-associated gene (ICP34.5) of herpes simplex virus. In all three proteins, a centrally located acidic region precedes a highly conserved, hydrophilic 56-amino-acid domain located at the carboxy terminus. LMW23-NL predicts a highly basic protein of 184 amino acids with an estimated molecular mass of 21.3 kDa. The similarity of LMW23-NL to genes involved in myeloid cell differentiation and viral host range suggests a role for it in African swine fever virus host range.